Angiopoietin 2 stimulates trophoblast invasion via a mechanism associated with JNK signaling. (24th February 2021) - Hou, Huomei; Ning, Fen; Zhang, Joy Yue; Lu, Qinsheng; Zhang, Min; Wu, Peihuang; Chen, Miaojuan; Lash, Gendie E
Abstract: Extravillous trophoblast cell (EVT) invasion is tightly controlled, and its dysregulation can lead to altered spiral artery remodeling and contribute to a number of different pregnancy complications. Angiopoietin-2 (Ang-2) is expressed by trophoblast cells and various cells in the decidua, and trophoblast cells express its receptor, Tie2. Ang-2 has been shown to play roles in tumor progression and metastasis but it is not known if it also regulates EVT invasion. Here, we show that both the HTR-8/SVneo cell line and primary isolates of human EVT expressed various integrins and the Tie2 receptor, and Ang-2 stimulated their migration and/or invasion. Ang-2 increased expression of matrix metalloproteinase (MMP)2 and MMP9, altered the cytoskeleton of HTR-8/SVneo cells and also induced phosphorylation of Tie2, JNK and c-Jun. Inhibition of p-JNK (using SP600125) blocked the Ang-2 induced invasion of HTR-8/SVneo cells. In addition, inhibition of Tie2 (pexmetinib) and integrin signaling (RGDS and ATN-161) also blocked Ang-2-induced invasion. In conclusion, we demonstrate that Ang-2 can stimulate EVT invasion via a mechanism associated with activation of both the Tie2 receptor and integrins, which appear to work through different pathways; Tie2 through the JNK/c-JUN pathway and integrins through an as yet unidentified pathway(s). We therefore propose that any alterations in Ang-2 expression in the decidua would lead to an imbalance in pro- and anti-invasive factors, disrupting regulation of EVT invasion and spiral artery remodeling and thereby contribute to the etiology of several complications of pregnancy.